Green cementing material based on industrial solid waste activation and preparation method

CN122586410APending Publication Date: 2026-08-18WUHAI SAIMA CEMENT CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610938068.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-26
Publication Date
2026-08-18

AI Technical Summary

Technical Problem

[0005]但是,现有矿渣应用技术大多采用较高掺量方式,通常矿渣用量达到10%以上甚至更高

Benefits of technology

本发明采用低掺量粒化高炉矿渣粉,在保证早期强度基本不降低的前提下,提高了固井材料的致密性和封隔性能;通过联合粉磨工艺实现矿渣机械活化,提高矿渣利用效率;矿渣微粉的微填充作用能够减少材料内部孔隙数量,降低渗透率;利用工业固废替代部分熟料,实现资源综合利用,降低生产过程碳排放;工艺简单,无需额外热处理或化学激发处理,便于现有油井水泥生产线直接实施。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122586410A_ABST
    Figure CN122586410A_ABST
Patent Text Reader

Abstract

This invention discloses a green cementing material based on industrial solid waste activation and its preparation method. The green cementing material comprises the following components by weight percentage: 88-96% oil well clinker, 2-6% natural gypsum, and 2-8% granulated blast furnace slag powder, wherein the granulated blast furnace slag powder has a specific surface area of ​​400-500 m² / kg and a median particle size D50 of 5-10 μm. The preparation method includes: feeding the oil well clinker, natural gypsum, and granulated blast furnace slag powder into a grinding equipment in a certain proportion for joint grinding, so that the specific surface area of ​​the resulting mixed powder reaches 340-380 m² / kg, and then homogenizing it to obtain the green cementing material. This invention utilizes a low-dosage granulated blast furnace slag powder to replace part of the oil well clinker, and achieves mechanical activation of the slag through joint grinding. While ensuring the early strength of the cementing material, it improves the material's density and sealing performance, reduces permeability, and realizes the resource utilization of industrial solid waste. It has the advantages of simple process, easy industrial implementation, and green and low-carbon characteristics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of cementing materials for oil and gas wells, and in particular to a green cementing material based on the activation of industrial solid waste and its preparation method. Background Technology

[0002] Cementing is a crucial step in the drilling and completion of oil, natural gas, shale gas, coalbed methane, and geothermal wells. Its primary function is to form a cement stone structure with sufficient strength and sealing performance between the casing and the wellbore, thereby achieving formation isolation, casing support, and preventing oil, gas, and water cross-contamination. The quality of cementing directly affects the service life, production efficiency, and safety of oil and gas wells; therefore, the performance of cementing materials is of paramount importance in oil and gas well engineering.

[0003] Currently, G-grade or H-grade oil well cement is widely used as the main cementing material in oil and gas well cementing projects both domestically and internationally. According to existing technologies, oil well cement is typically produced by grinding oil well clinker and natural gypsum together, with the oil well clinker content generally being 90-95% and the natural gypsum content generally being 5-10%. The main function of natural gypsum is to regulate the hydration rate of clinker minerals, especially tricalcium aluminate, thereby preventing flash setting of the cement paste and ensuring construction safety and operability. However, the existing clinker-gypsum system still has some shortcomings. First, the production process of oil well clinker requires high-temperature calcination, typically reaching around 1450℃, resulting in significant energy consumption and substantial carbon dioxide emissions, which is detrimental to current requirements for energy conservation, emission reduction, and green low-carbon development. Second, the cement stone formed by the traditional clinker-gypsum system mainly consists of hydrated calcium silicate gel (CSH) and calcium hydroxide crystals. As the curing time increases, the later hydration reaction gradually slows down, and the strength increase tends to plateau, making it difficult to further improve material performance. Furthermore, due to the presence of a certain number of capillary pores and interconnected pores within the cement stone, fluid seepage channels can easily form in complex downhole environments, thereby affecting the sealing effect between the casing and the formation, and even leading to oil, gas and water cross-flow.

[0004] In recent years, with the development of industrial solid waste resource utilization technologies, granulated blast furnace slag, as a typical industrial solid waste, has gradually attracted attention. Granulated blast furnace slag is a byproduct of the ironmaking industry, which forms a glassy structure with potential hydraulic activity after water quenching and rapid cooling. Existing research shows that slag powder can be used as a mineral admixture in the field of building materials, participating in hydration reactions and improving material properties under certain conditions.

[0005] However, most existing slag application technologies employ high slag content, typically exceeding 10% or even higher. For oil well cementing materials, excessively high slag content leads to a reduction in clinker proportion, thus affecting early strength development and failing to meet the requirements of cementing projects for early strength and construction cycle.

[0006] Therefore, how to achieve the resource utilization of industrial solid waste and improve the compactness and sealing performance of materials while ensuring that the early strength of oil well cementing materials is not reduced, has become an urgent technical problem to be solved in this field. Summary of the Invention

[0007] The purpose of this invention is to overcome the shortcomings of existing technologies and provide a green cementing material based on the activation of industrial solid waste and its preparation method. This invention introduces low-dosage granulated blast furnace slag powder into a traditional oil well clinker and gypsum system, and employs a combined grinding process to achieve mechanical activation. This maintains the early strength of the cementing material while improving its density and sealing performance, thus realizing the resource utilization of industrial solid waste.

[0008] To achieve the above objectives, the present invention adopts the following technical solution: A green cementing material based on industrial solid waste activation comprises the following components by weight percentage: Oil well clinker content: 88-96%; 2-6% natural gypsum; Granulated blast furnace slag powder 2-8%; The granulated blast furnace slag powder has a specific surface area of ​​400-500 m² / kg and a median particle size D50 of 5-10 μm. The granulated blast furnace slag powder is combined with oil well clinker and natural gypsum to form a mixed powder, and the specific surface area of ​​the mixed powder is 340-380 m² / kg.

[0009] Furthermore, the granulated blast furnace slag powder is obtained by grinding water-quenched granulated blast furnace slag.

[0010] Furthermore, the natural gypsum is natural dihydrate gypsum or natural anhydrite, wherein the sulfur trioxide content is not less than 40%.

[0011] Furthermore, the oil well clinker is a Grade G or Grade H oil well cement clinker that meets the requirements of GB / T10238 standard, and the specific surface area of ​​the green cementing material is 340-380 m² / kg.

[0012] This invention also provides a method for preparing a green cementing material based on industrial solid waste activation, comprising the following steps: S1. Add oil well clinker, natural gypsum and granulated blast furnace slag powder into the grinding equipment in proportion; S2. Perform combined grinding to achieve a specific surface area of ​​340-380 m² / kg for the resulting mixed powder; S3. The mixed powder obtained in step S2 is homogenized to obtain the finished green cementing material.

[0013] Furthermore, in step S2, the grinding equipment is a ball mill.

[0014] Furthermore, in step S2, the co-grinding time is 20 to 50 minutes.

[0015] Furthermore, the compressive strength of the prepared green cementing material is not less than 14 MPa under curing conditions at 60℃ for 24 hours.

[0016] Compared with the prior art, the beneficial effects of the present invention are: This invention uses low-dosage granulated blast furnace slag powder, which improves the compactness and sealing performance of cementing materials while ensuring that the early strength is not significantly reduced. The mechanical activation of slag is achieved through a combined grinding process, which improves the utilization efficiency of slag. The micro-filling effect of slag powder can reduce the number of pores inside the material and reduce the permeability. Industrial solid waste is used to replace part of the clinker, realizing comprehensive resource utilization and reducing carbon emissions in the production process. The process is simple and does not require additional heat treatment or chemical activation treatment, making it easy to implement directly in existing oil well cement production lines. Attached Figure Description

[0017] To more clearly illustrate the technical solution of the present invention, the drawings used in the implementation examples will be briefly introduced below. Obviously, those skilled in the art can obtain other drawings based on these drawings without any creative effort.

[0018] Figure 1 This invention presents a green cementing material preparation process flow diagram based on industrial solid waste activation and its preparation method. Figure 2 This is a comparison chart of experimental data from embodiments and comparative examples of a green cementing material based on industrial solid waste activation and its preparation method proposed in this invention. Figure 3 The figures show a comparison of the 24-hour compressive strength of various embodiments and comparative examples of the green cementing material and its preparation method based on industrial solid waste activation proposed in this invention. Figure 4 This is a comparison chart of the 28-day permeability of various embodiments and comparative examples of the green cementing material and preparation method based on industrial solid waste activation proposed in this invention. Detailed Implementation

[0019] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments and comparative examples. It should be noted that the embodiments described below are only for explaining the invention and do not constitute a limitation on the scope of protection of this invention. Any modifications, equivalent substitutions, improvements, etc., made by those skilled in the art based on the content of this invention within the spirit and principles of this invention should be included within the scope of protection of this invention.

[0020] Please see the appendix Figure 1-4 This invention uses oil well clinker, natural gypsum, and granulated blast furnace slag powder as main raw materials. Oil well clinker is the main cementing component of the green cementing material of this invention. Oil well clinker is typically obtained by high-temperature calcination of limestone, clay, and iron-containing corrective materials. Its mineral composition mainly includes tricalcium silicate (C3S), dicalcium silicate (C2S), tricalcium aluminate (C3A), and tetracalcium aluminoferrite (C4AF).

[0021] Tricalcium silicate is the main mineral that forms early strength and has a faster hydration rate than other minerals; dicalcium silicate mainly contributes to later strength; tricalcium aluminate can form ettringite in the presence of gypsum, thereby regulating the setting time; and tetracalcium aluminoferrite participates in the hydration of the system and improves the clinker firing performance.

[0022] Natural gypsum, used as a setting regulator, is primarily composed of calcium sulfate. During the initial hydration stage, natural gypsum reacts with tricalcium aluminate to form ettringite, thus preventing flash setting caused by rapid tricalcium aluminate hydration and ensuring the cementing slurry has good workability.

[0023] Granulated blast furnace slag powder originates from blast furnace slag produced in the ironmaking industry. After being rapidly cooled by water in a high-temperature molten state, blast furnace slag forms a large number of glassy structures, which are rich in active calcium oxide, silicon dioxide, and alumina, and have potential hydraulic activity.

[0024] Because the vitreous structure of slag is relatively stable, its activity is difficult to fully realize under conventional conditions. Therefore, this invention employs a combined grinding method for mechanical activation. Through the impact, friction, and shear forces generated by the ball mill, numerous fresh fracture surfaces and active sites are created on the surface of the slag particles, thereby enhancing the slag activity.

[0025] During the hydration process of cementing materials, the oil well clinker first reacts with water to generate a large amount of hydrated calcium silicate gel and calcium hydroxide. As the hydration process continues, the active components in the slag gradually participate in the reaction, forming new cementing products in the alkaline environment of the system, thereby improving the structural integrity of the cementing material.

[0026] At the same time, slag particles are smaller than clinker particles, which can fill the pores between clinker particles and between hydration products, increase particle packing density, reduce the number of interconnected pores, reduce fluid seepage channels, and thus improve the sealing performance of cementing materials.

[0027] Specifically, in this embodiment, the oil well clinker is Grade G high sulfate-resistant oil well cement clinker produced by a certain cement plant, with the following mineral composition: C3S: 58.2%, C2S: 19.5%, C3A: 2.8%, C4AF: 13.5%, and free CaO: 0.8%.

[0028] Natural gypsum: Natural dihydrate gypsum, with a CaSO4·2H2O content of 92% and an SO3 content of 42.5%.

[0029] Granulated blast furnace slag powder: The raw material is water-quenched blast furnace slag with an activity index (28d) of 98%. The specific surface area is 380-450 m² / kg, and the corresponding D50 is 5-10 μm.

[0030] Cement slurry was prepared according to API Spec 10A with a water-cement ratio of 0.44 and a curing temperature of 60℃. Compressive strength was measured using a 50mm cube mold; thickening time was measured using a high-temperature, high-pressure thickener (52℃ / 36.5MPa).

[0031] Example 1 Formula (by weight percentage): Oil well clinker: 92.5%; Natural gypsum: 3.5%; Granulated blast furnace slag powder: 4%; Preparation steps: S1. Crush the oil well clinker, natural gypsum, and natural gypsum into 5mm pieces using a jaw crusher.

[0032] S2. Weigh out the oil well clinker, natural gypsum powder and slag powder according to the proportion (slag pre-powder specific surface area 410 m² / kg, D50=8.5 μm).

[0033] S3. The three materials were fed into a Φ500×500mm test ball mill with a ball-to-material ratio of 8:1 and a rotation speed of 45 rpm for 35 minutes. The specific surface area of ​​the output was measured to be 350 m² / kg.

[0034] S4. Homogenize in a V-type mixer for 15 minutes to obtain the finished product.

[0035] After testing, the compressive strength at 24 hours was 14.8 MPa, the permeability at 28 days was 0.031 mD, the thickening time (52℃ / 38MPa) was 118 min, and the free liquid content was 3.2%. Example 2 (5% slag content, higher fineness) Mixing ratio: Oil well clinker: 91% Natural gypsum: 4% Granulated blast furnace slag powder: 5% (specific surface area 410m² / kg, D50=8.5 μm) Preparation steps: Same as in Example 1, co-milling time 37 minutes, output specific surface area 351 m² / kg.

[0036] After testing, the strength was 15.2 MPa at 24 hours and the permeability was 0.025 mD at 28 days.

[0037] Example 3 (Slag content 3%, lower limit) Mixing ratio: Oil well clinker: 94%; Natural gypsum: 3%; Granulated blast furnace slag powder: 3% (specific surface area 410 m² / kg, D50=8.5 μm); Preparation steps: co-mill for 34 minutes, output specific surface area 348 m² / kg.

[0038] After testing, the 24-hour strength was 14.5 MPa, and the 28-day permeability was 0.035 mD. Comparative Example 1 (pure clinker-gypsum, no slag) Formula: 96% oil well clinker, 4% natural gypsum. Grind separately and then mix (clinker + gypsum are ground together to a specific surface area of ​​350m² / kg, without adding slag).

[0039] After testing, the 24-hour strength was 14.1 MPa, and the 28-day permeability was 0.052 mD.

[0040] Comparative Example 2 (slag content was the same, but the samples were not co-ground and were directly mixed). Formula: Same as in Example 1 (92.5 / 3.5 / 4), clinker and gypsum (specific surface area 340 m² / kg) are ground separately to obtain oil well clinker powder and gypsum powder, which are then directly mechanically mixed with slag powder without co-grinding.

[0041] After testing, the 24-hour strength was 13.2 MPa, and the 28-day permeability was 0.048 mD.

[0042] Comparative Example 3 (10% slag content, high content, co-grinding) Formula: 86.5% oil well clinker, 3.5% natural gypsum, and 10% slag (fineness same as in Example 1).

[0043] After testing, the 24-hour intensity was 12.5 MPa (significantly reduced). Therefore, high slag content will dilute the clinker and reduce its early strength, making it unsuitable for the stringent early strength requirements of cementing.

[0044] Based on the above embodiments and comparative examples, the appendix is ​​derived. Figure 2-4 Based on the comparative data in the table, we can conclude that: 1. The low-dosage (3~5%) ultrafine slag co-grinding system of the present invention has a strength at 60℃ that is 5~7.8% higher than that of the slag-free system, and a lower permeability.

[0045] 2. The co-grinding process has a significantly better mixing effect than the fractional grinding process (comparison of Example 1 and Comparative Example 2), demonstrating the importance of mechanochemical activation.

[0046] 3. Adding more than 8% will impair early strength and is therefore detrimental.

[0047] This invention can be implemented directly on existing oil well cement grinding production lines, requiring only the addition of slag ultrafine grinding equipment or co-grinding of slag with clinker and gypsum. It is suitable for cementing projects of various oil and gas wells, especially for deep wells with high requirements for later strength and sealing.

[0048] Through examples and appendices Figure 1 The comparative test results show that: Examples 1, 2, and 3 all used a low-content slag co-grinding system. While maintaining the 24-hour compressive strength to meet the cementing requirements, the permeability was significantly lower than that of Comparative Example 1 and Comparative Example 2.

[0049] In this example, the formulations of Example 1 and Comparative Example 2 are exactly the same, only the processes are different. Example 1 uses a co-grinding process, and the compressive strength reaches 14.8 MPa after 24 hours, while that of Comparative Example 2 is only 13.2 MPa, indicating that co-grinding can effectively improve the utilization efficiency of slag.

[0050] Compared with Comparative Example 1, under the condition of maintaining similar early strength, the permeability of Example 1 decreased from 0.052mD to 0.031mD, indicating that the introduction of low-content slag can effectively improve the internal structure of cementing stone and increase the density of the material.

[0051] Example 3 shows that when the slag content is reduced to 3%, it can still maintain good strength and permeability.

[0052] Comparative Example 3 shows that when the slag content is increased to 10%, the 24-hour compressive strength decreases to 12.5 MPa, indicating that excessive slag content will weaken the early strength advantage of the clinker system and is not conducive to cementing engineering applications.

[0053] This invention employs a combined grinding process for oil well clinker, natural gypsum, and granulated blast furnace slag powder. Compared to the process of grinding separately and then mixing, the combined grinding process subjectes all components to mechanical forces simultaneously, achieving not only uniform mixing but also increased slag activation. During ball milling, steel balls continuously impact and compress the material, causing particle breakage. Due to the differences in hardness among clinker, gypsum, and slag, a more reasonable particle size distribution is formed during grinding. Simultaneously, new fracture surfaces are continuously generated on the slag particle surface, increasing surface free energy and enhancing reactivity. The mixed powder obtained from combined grinding exhibits a more uniform particle distribution and a higher particle contact probability, which is beneficial for subsequent hydration reactions. The results of examples and comparative examples show that, under the same formulation conditions, the compressive strength of the co-grinding system is significantly higher than that of the separately ground and mixed system, indicating that combined grinding can effectively improve slag utilization efficiency.

[0054] The green cementing material of this invention can be directly produced using existing oil well cement production lines. The production process requires no additional high-temperature calcination equipment or chemical activators; production can be completed simply by adding granulated blast furnace slag powder to the existing grinding system and implementing combined grinding. Therefore, this invention has advantages such as simple process, strong equipment adaptability, and low production cost. The green cementing material prepared by this invention is suitable for various cementing projects, including oil wells, natural gas wells, shale gas wells, coalbed methane wells, geothermal wells, and water injection wells, and is particularly suitable for deep wells and complex well environments with high sealing performance requirements. Replacing part of the clinker with industrial solid waste not only achieves comprehensive resource utilization but also helps reduce carbon emissions per unit product, resulting in good economic and social benefits.

[0055] It should be noted that the above embodiments are only used to illustrate the present invention and are not intended to limit the scope of protection of the present invention. Various modifications, equivalent substitutions, and improvements made by those skilled in the art without departing from the spirit and substance of the present invention should fall within the scope of protection of the present invention.

Claims

1. A green cementing material based on the activation of industrial solid waste, characterized in that, Includes the following components by weight percentage: Oil well clinker content: 88-96%; 2-6% natural gypsum; Granulated blast furnace slag powder 2-8%; The granulated blast furnace slag powder has a specific surface area of ​​400-500 m² / kg and a median particle size D50 of 5-10 μm. The granulated blast furnace slag powder is combined with oil well clinker and natural gypsum to form a mixed powder, and the specific surface area of ​​the mixed powder is 340-380 m² / kg.

2. The green cementing material based on industrial solid waste activation according to claim 1, characterized in that: The granulated blast furnace slag powder is obtained by grinding water-quenched granulated blast furnace slag.

3. The green cementing material based on industrial solid waste activation according to claim 1, characterized in that: The natural gypsum is natural dihydrate gypsum or natural anhydrite, wherein the sulfur trioxide content is not less than 40%.

4. The green cementing material based on industrial solid waste activation according to claim 1, characterized in that: The specific surface area of ​​the green cementing material is 340–380 m² / kg.

5. A method for preparing a green cementing material based on industrial solid waste activation according to any one of claims 1 to 4, characterized in that, Includes the following steps: S1. Add oil well clinker, natural gypsum and granulated blast furnace slag powder into the grinding equipment in proportion; S2. Perform combined grinding to achieve a specific surface area of ​​340-380 m² / kg for the resulting mixed powder; S3. The mixed powder obtained in step S2 is homogenized to obtain the finished green cementing material.

6. The method for preparing a green cementing material based on industrial solid waste activation according to claim 5, characterized in that: In step S2, the grinding equipment is a ball mill.

7. The method for preparing a green cementing material based on industrial solid waste activation according to claim 5, characterized in that: In step S2, the co-grinding time is 20 to 50 minutes.

8. The method for preparing a green cementing material based on industrial solid waste activation according to claim 5, characterized in that: The green cementing material produced has a compressive strength of no less than 14 MPa under curing conditions of 60℃ for 24 hours.